The Crucial of Students’ Self-Actualization in Teacher Talk Framework to Increase the Students Speaking Skill - Muflihatun Haqiqiyah (Institut Agama Islam Negeri Madura, 2021)
Every teacher should have an appropriate teaching method, including speaking. One of the indispensable parts of foreign language teaching, especially in speaking skills, is teacher talk. Students need teacher talk that is elaborated with the entire self-actualization in increasing their speaking skill. The research was intended to know how the teacher talk's theoretical framework used by the teacher to increase students self-actualization in speaking performance. This research was descriptive qualitative research because it described teacher talk between the teacher and students in the classroom. The data collection instruments were observation and interview. This research showed that students are more active in expressing their ideas, and the classroom was more harmonious. Some of them also were more confident to convey information to the teacher without asked. It can be concluded that teacher talk is essential in increasing self-actualization to get better performance in speaking English.